Implementasi Sistem Pemesanan Laundry Berbasis Web pada UMKM Bee Laundry Menggunakan Metode RAD - Daffa Annisa Hidayatul Ays Sujianto; Mardiana Andarwati (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
This study develops and evaluates a web-based laundry ordering information system for Bee Laundry, a micro, small, and medium enterprise (MSME) that previously relied on manual processes in managing orders and transactions. These manual practices caused data inaccuracies, recording errors, and limited service monitoring. To address this gap, this research applies the Rapid Application Development (RAD) approach to deliver a practical, low-cost, and user-oriented system tailored to MSME operational constraints. The proposed system integrates order management, automated transaction recording, service status tracking, and customer data management into a single platform. System evaluation was conducted using Blackbox Testing and Task-Based Usability Testing. The results indicate that the system achieves a 100% task success rate, time efficiency of 0.92 tasks per minute, and a 0% defect rate. This study demonstrates that combining Rapid Application Development with task-based usability testing effectively supports digital transformation in small-scale laundry MSMEs.